Sodium butyrate attenuated neuronal apoptosis via GPR41/Gβγ/PI3K/Akt pathway after MCAO in rats. Issue 2 (February 2021) - Zhou, Zhenhua; Xu, Ningbo; Matei, Nathanael; McBride, Devin W; Ding, Yan; Liang, Hui; Tang, Jiping; Zhang, John H
Sodium butyrate, a short-chain fatty acid, is predominantly produced by gut microbiota fermentation of dietary fiber and serves as an important neuromodulator in the central nervous system. Recent experimental evidence has suggested that sodium butyrate may be an endogenous ligand for two orphan G protein-coupled receptors, GPR41 and GP43, which regulate apoptosis and inflammation in ischemia-related pathologies, including stroke. In the present study, we evaluated the potential efficacy and mechanism of action of short-chain fatty acids in a rat model of middle cerebral artery occlusion (MCAO). Fatty acids were intranasally administered 1 h post MCAO. Short-chain fatty acids, especially sodium butyrate, reduced infarct volume and improved neurological function at 24 and 72 h after MCAO. At 24 h, the effects of MCAO, increased apoptosis, were ameliorated after treatment with sodium butyrate, which increased the expressions of GPR41, PI3K and phosphorylated Akt. To confirm these mechanistic links and characterize the GPR active subunit, PC12 cells were subjected to oxygen–glucose deprivation and reoxygenation, and pharmacological and siRNA interventions were used to reverse efficacy. Taken together, intranasal administration of sodium butyrate activated PI3K/Akt via GPR41/Gβγ and attenuated neuronal apoptosis after MCAO.